2005
DOI: 10.1073/pnas.0508124102
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency of t e lomerase reverse transcriptase leads to anticipation in autosomal dominant dyskeratosis congenita

Abstract: Dyskeratosis congenita is a rare inherited disorder characterized by abnormal skin manifestations. Morbidity and mortality from this disease is usually due to bone marrow failure, but idiopathic pulmonary fibrosis and an increased cancer predisposition also occur. Families with autosomal dominant dyskeratosis congenita display anticipation and have mutations in the telomerase RNA gene. We identified a three-generation pedigree with autosomal dominant dyskeratosis congenita, anticipation, and telomere shortenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
417
1
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 419 publications
(435 citation statements)
references
References 28 publications
10
417
1
4
Order By: Relevance
“…In this family, the IPF phenotype was most common (21). Mutations in TERT are now recognized to be the most prevalent cause of familial pulmonary fibrosis (16).…”
Section: Telomerase and Telomere Gene Mutations Explain The Genetic Bmentioning
confidence: 80%
See 2 more Smart Citations
“…In this family, the IPF phenotype was most common (21). Mutations in TERT are now recognized to be the most prevalent cause of familial pulmonary fibrosis (16).…”
Section: Telomerase and Telomere Gene Mutations Explain The Genetic Bmentioning
confidence: 80%
“…The role of telomerase genetics in familial lung disease came first from a study of a three-generation family that was found to carry a deleterious mutation in the telomerase reverse transcriptase gene, TERT (21). In this family, the IPF phenotype was most common (21).…”
Section: Telomerase and Telomere Gene Mutations Explain The Genetic Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterozygous mutations in hTR, which reduce its accumulation and perturb its structure, lead to an autosomal dominant form of DC through haploinsufficiency of the RNA subunit (5,14,45). Similarly, haploinsufficiency of TERT has been implicated in DC and in aplastic anemia (1,47,51). Limiting abundance of telomerase subunits may help to facilitate the fine balance of telomerase repression and activation associated with differentiated cells and their stem cell progenitors (15).…”
mentioning
confidence: 99%
“…11,12 Autosomal dominant forms of DC are caused by mutations in TERT, TERC or the telomere binding protein TIN2, providing a clear link between telomere shortening and the pathophysiology of DC. [13][14][15][16] Several dedicated cofactors associate with dyskerin and are required for telomerase RNP assembly and function. Many of these, such as NAF1, pontin and reptin, aid in RNP assembly but do not remain associated with the mature telomerase enzyme.…”
mentioning
confidence: 99%